Adverse Events of Postoperative Thoracic Epidural Analgesia: A Retrospective Analysis of 7273 Cases in a Tertiary Care Teaching Hospital. Issue 1 (February 2017) - von Hösslin, T.; Imboden, P.; Lüthi, A.; Rozanski, M. J.; Schnider, T. W.; Filipovic, M.
Abstract : (Abstracted from Eur J Anaesthesiol, 2016;33(10):708–714) An effective and well-established technique for postoperative pain relief following major abdominal and thoracic surgery is thoracic epidural analgesia (tEDA). The occurrence of epidural hematoma and abscess, which may in turn cause transient or permanent neurologic deficit, is the major safety concern for this technique.